2020
DOI: 10.1177/1078155220940043
|View full text |Cite
|
Sign up to set email alerts
|

Real-world evidence of poly ADP-ribose polymerase inhibitors in the treatment of ovarian cancer: A systematic literature review

Abstract: Objective The treatment landscape for ovarian cancer has shifted in recent years with the approval of poly ADP-ribose polymerase inhibitors in 2014. Most patients with ovarian cancer have advanced disease at diagnosis. Understanding how treatments for advanced disease work in real-world settings must be assessed to provide care for these patients. Therefore, the objective of this study was to locate and assess real-world studies measuring the safety and effectiveness of poly ADP-ribose polymerase inhibitors an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…RCT data suggest differences between PARPi in terms of tolerability and dose modifications [15][16][17][18]. Real-world evidence of PARPi use in clinical practice reported a safety profile largely consistent with RCT data [19][20][21][22][23][24], with emerging data supporting distinct tolerability profiles for each PARPi [25]. Tolerability is likely to be an important factor for long-term PARPi maintenance therapy.…”
Section: Introductionmentioning
confidence: 61%
“…RCT data suggest differences between PARPi in terms of tolerability and dose modifications [15][16][17][18]. Real-world evidence of PARPi use in clinical practice reported a safety profile largely consistent with RCT data [19][20][21][22][23][24], with emerging data supporting distinct tolerability profiles for each PARPi [25]. Tolerability is likely to be an important factor for long-term PARPi maintenance therapy.…”
Section: Introductionmentioning
confidence: 61%
“…29 Other real world studies with olaparib have reported a median PFS ranging from 12.7 to 15.6 months and a median OS ranging from 30.9 to 35.4 months. 22-28 Although our study was not able to determine OS, these survival data should be interpreted with caution taking into account the line of therapy and other factors such as HRD status.…”
Section: Discussionmentioning
confidence: 78%
“…Other real word evidence studies have looked at PARPi, mostly olaparib. 22-28 A retrospective review in Italy investigated the use of olaparib as maintenance therapy in patients with BRCA 1/2 mutated recurrent platinum sensitive ovarian cancer in 234 patients. They found the most frequently reported toxicities were nausea (35.7%), anemia (35.7%), and fatigue (35.1%), with anemia (5.6%) being the most common grade ≥3 toxicity.…”
Section: Discussionmentioning
confidence: 99%